2008
DOI: 10.1007/s11255-008-9417-9
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic profile, premature ejaculation, erectile function and andropause in an at-risk Mexican population

Abstract: A total of 1,779 men with an average age of 56.6 years were included in the study. The average prostate-specific antigen value in the sample was 1.73 (n = 1,316). Prostatic symptomatology in accordance with the international prostate symptom score was 7.96 points. A total of 41.9% of participants reported experiencing PE. The average time to reach ejaculation was 10.97 min. Of the participating individuals, 39.5% were diagnosed with andropause. Prostatic symptomatology was associated with risk factors of age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The increase of the age in patients with LUTS does not represent a protective factor for PE, in fact, another study conducted on 1779 men with a mean age 56 years and a mean IPSS score (International prostate symptoms score) = 7.96 points, showed a prevalence of PE 41% 22. In young patients with P, the frequency of PE seems to be increasing among the younger patients as demonstrated by the study of Qiu: 42.9%, 37.0%, and 35.7% in the 18–30, 30–40, and 40–57 years age groups, respectively 23…”
Section: Discussionmentioning
confidence: 93%
“…The increase of the age in patients with LUTS does not represent a protective factor for PE, in fact, another study conducted on 1779 men with a mean age 56 years and a mean IPSS score (International prostate symptoms score) = 7.96 points, showed a prevalence of PE 41% 22. In young patients with P, the frequency of PE seems to be increasing among the younger patients as demonstrated by the study of Qiu: 42.9%, 37.0%, and 35.7% in the 18–30, 30–40, and 40–57 years age groups, respectively 23…”
Section: Discussionmentioning
confidence: 93%
“…EjD increases with advancing age. 17,18 In our study, the factor most closely associated with EjD was age; as age increased, the incidence of EjD and PE increased. In other words, the ability to ejaculate during sex decreased and the frequency of dry ejaculation increased with aging.…”
Section: Discussionmentioning
confidence: 46%
“…15,16 Similar results by age groups were also reported by the Brazilian Sexual Life Study: PE was reported in 25.8% of 3332 Brazilian men. 17 JaspersenGastelum et al 18 reported a high prevalence rate in older age groups. They reported that PE was present in 46.9% of 1011 patients, and was more frequent in the age range of 51 --60 years (43.3%), followed by the age range of 61 --70 years (26%).…”
Section: Discussionmentioning
confidence: 99%